2019
DOI: 10.3390/ma12182847
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Lignin Diversity on the Structural and Thermal Properties of Polymeric Microspheres Derived from Lignin, Styrene, and/or Divinylbenzene

Abstract: This work investigates the impact of lignin origin and structural characteristics, such as molecular weight and functionality, on the properties of corresponding porous biopolymeric microspheres obtained through suspension-emulsion polymerization of lignin with styrene (St) and/or divinylbenzene (DVB). Two types of kraft lignin, which are softwood (Picea abies L.) and hardwood (Eucalyptus grandis), fractionated by common industrial solvents, and related methacrylates, were used in the synthesis. The presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…There are the similar rules in Figure 2 F–J and Figure 2 K–O. These pores are an important basis for biochar to have larger surface area and stronger adsorption performance [ 18 , 42 ]. Comparing Figure 2 A,F,K, it is found that the images are very similar, which shows that pyrolysis time has little effect on the pore structure of CB.…”
Section: Resultsmentioning
confidence: 84%
“…There are the similar rules in Figure 2 F–J and Figure 2 K–O. These pores are an important basis for biochar to have larger surface area and stronger adsorption performance [ 18 , 42 ]. Comparing Figure 2 A,F,K, it is found that the images are very similar, which shows that pyrolysis time has little effect on the pore structure of CB.…”
Section: Resultsmentioning
confidence: 84%
“…Another confirmation of the occurrence of maleation reaction is a peak observed around 1621 cm −1 in modified lignin. It corresponds to the addition of a double bond C=C of maleic anhydride [24]. An intensified peak near 1159 cm −1 corresponding to C-O symmetric stretching also confirms the occurrence of maleation [25].…”
Section: Mechanical Properties Of Lignin-based Compositesmentioning
confidence: 74%
“…This issue includes five articles on polyurethanes blended with various types of additives [1][2][3][4][5], of which two papers discusses the polyurethane systems partly prepared from naturally-derived components, such as lignin [5] or naturally-derived polyols [4]. Four papers discuss the preparation of synthetic unsaturated polyester resins reinforced with natural fillers [6][7][8][9], and two other papers are focused on the modification of polyolefins (PE,PP) to improve their strength properties [10,11]. One work is concerned with the preparation of biochar and bio-oil from biomass, where the potential uses of both types of products are discussed [12]; the other paper considers the modification of cotton linter for use as efficient adsorbent for the phosphate.…”
Section: Short Description Of the Articles Presented In This Special Issuementioning
confidence: 99%
“…The paper of Goliszek, Podkościelna, Sevastyanova, Gawdzik, and Chabros ("The Influence of Lignin Diversity on the Structural and Thermal Properties of Polymeric Microspheres Derived from Lignin, Styrene, and/or Divinylbenzene" [9]) investigates the impact of lignin influence on the properties of the porous biopolymeric microspheres. It was found that the materials have a high thermal resistance and the incorporation of methacrylated lignin into the microspheres resulted in an increase of specific surface area and porosity.…”
Section: Short Description Of the Articles Presented In This Special Issuementioning
confidence: 99%